Respuesta :
Answer:
The average velocity is
[tex]266\frac{m}{s},274\frac{m}{s}[/tex] and [tex]117\frac{m}{s}[/tex] respectively.
Explanation:
Let's start writing the vertical position equation :
[tex]L(t)=2t^{3}+t^{2}-5t+1[/tex]
Where distance is measured in meters and time in seconds.
The average velocity is equal to the position variation divided by the time variation.
[tex]V_{avg}=\frac{Displacement}{Time}[/tex] = Δx / Δt = [tex]\frac{x2-x1}{t2-t1}[/tex]
For the first time interval :
t1 = 5 s → t2 = 8 s
The time variation is :
[tex]t2-t1=8s-5s=3s[/tex]
For the position variation we use the vertical position equation :
[tex]x2=L(8s)=2.(8)^{3}+8^{2}-5.8+1=1049m[/tex]
[tex]x1=L(5s)=2.(5)^{3}+5^{2}-5.5+1=251m[/tex]
Δx = x2 - x1 = 1049 m - 251 m = 798 m
The average velocity for this interval is
[tex]\frac{798m}{3s}=266\frac{m}{s}[/tex]
For the second time interval :
t1 = 4 s → t2 = 9 s
[tex]x2=L(9s)=2.(9)^{3}+9^{2}-5.9+1=1495m[/tex]
[tex]x1=L(4s)=2.(4)^{3}+4^{2}-5.4+1=125m[/tex]
Δx = x2 - x1 = 1495 m - 125 m = 1370 m
And the time variation is t2 - t1 = 9 s - 4 s = 5 s
The average velocity for this interval is :
[tex]\frac{1370m}{5s}=274\frac{m}{s}[/tex]
Finally for the third time interval :
t1 = 1 s → t2 = 7 s
The time variation is t2 - t1 = 7 s - 1 s = 6 s
Then
[tex]x2=L(7s)=2.(7)^{3}+7^{2}-5.7+1=701m[/tex]
[tex]x1=L(1s)=2.(1)^{3}+1^{2}-5.1+1=-1m[/tex]
The position variation is x2 - x1 = 701 m - (-1 m) = 702 m
The average velocity is
[tex]\frac{702m}{6s}=117\frac{m}{s}[/tex]